Identification of four novel variants that influence central corneal thickness in multi-ethnic Asian populations - Cornes, Belinda K.; Jonas, Jost B. (Human molecular genetics, 2012)
Abstract. Central corneal thickness (CCT) is a highly heritable trait. Genes that significantly influence CCT can be candidate genes for common disorders in which CCT has been implicated, such as primary open-angle glaucoma (POAG) and keratoconus. Because the genetic factors controlling CCT in different Asian populations are unclear, we have built on previous work conducted on Singaporean Indians and Malays and extended our hypothesis to individuals of Chinese descent. We have followed up on all suggestive signals of association with CCT (P < 10−4) from the previously reported meta-analysis comprising Indians and Malays in a sample of Chinese individuals (n= 2681). In the combined sample (n= 7711), strong evidence of association was observed at four novel loci: IBTK on chromosome 6q14.1; CHSY1 on chromosome 15q26.3; and intergenic regions on chromosomes 7q11.2 and 9p23 (8.01 × 10−11 < λGC corrected Pmeta < 8.72 × 10−8). These four new loci explain an additional 4.3% of the total CCT variance across the sample cohorts over and above that of previously identified loci. We also extend on a previous finding at a fifth locus (AKAP13) where a new single-nucleotide polymorphism (rs1821481, Pmeta = 9.99 × 10−9) was found to be significantly more informative compared with the previously reported rs6496932 (Pmeta = 3.64 × 10−5). Performing association analysis in Asians may lead to the discovery of ethnic-specific genes that control CCT, offering further mechanistic insights into the regulation of CCT. In addition, it may also provide several candidate genes for interrogation for POAG, keratoconus and possible racial/ethnic variations.